The Dynamics of Inter-Village Border Governance: A Case Study - Alexsander Yandra; David Wibowo; Arizal Arizal; Dian Rianita; Trio Saputra (Program Pascasarjana Universitas Negeri Makassar, 2023)
The ability of local governments to optimize existing resources is of course the key for regions in implementing regional autonomy. Law Number 23 of 2014 does not completely regulate the settlement of regional boundary disputes, but what regulates the determination and confirmation of territorial boundaries both on land and at sea is contained in the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 45 of 2016 concerning Guidelines for Determining and Affirming Village Boundary. Territorial border conflicts are things that often occur in several districts, cities and even villages. The dynamics of border governance between Penyengat Village and Rawa Mekar Jaya Village is a conflict that arises because of different views regarding the agreed boundaries. There are five indicators of border governance. The method used in this research is descriptive research method with a qualitative approach. Data collection techniques with literature study, in-depth interviews and observation. The results showed that the border management between Penyengat Village and Kampung Rawa Mekar Jaya had not been resolved as the government hoped, responsibility and equality in seeing the wishes of the community tended to be neglected. boundary.